Incorporação de probióticos na dieta para juvenis de tilápias-do-nilo: Parâmetros hematológicos, imunológicos e microbiológicos - Nakandakare, Ivan Bernardoni; Iwashita, Marina Keiko Pieroni [UNESP]; Dias, Danielle de Carla; Tachibana, Leonardo; Ranzani-Paiva, Maria José Tavares; Romagosa, Elizabeth (My University, 2013)
Probiotics are generally considered as live microorganisms which, when administered in adequate amounts, confer a health benefit to the host. The processing method of diet and the form of inclusion of probiotic can interfere in hematological, immunological and microbiological parameters in fish. The aim was to estimate the hematological, immunological and microbiological parameters in juveniles of Nile tilapia, fed probiotic, included before and after the process of pelletization and extrusion. The experimental design was completely randomized, with five treatments: pelleted diet without probiotic, pelleted diet with inclusion of probiotic before and after processing, extruded feed without probiotic and extruded feed with inclusion of probiotic after processing and five replications. Two hundred and fifty fish were distributed in 25 aquaria (20 L) and fed for 63 days. The blood composition (red and white) showed no significant differences except mean corpuscular hemoglobin concentration of control when compared to other treatments. The phagocytic capacity of the animals that had received the extruded diet supplemented with probiotic was significantly higher when compared to the other treatments. However, there were no differences between the treatments regarding to the phagocytic index. Fish fed the extruded diet exhibited significant improvement in the nonspecific immunity. The probiotic bacteria colonized the intestine, since it was possible to recover them. We can affirm that these fishes remained healthy, because the hematological parameters were not altered during the experimental. The study shows that any form type of inclusion in the feed tested (before or after and after pelletizing extrusion) may be easily used by the fish farmer.
Incorporation of probiotics in the diet for juvenile Nile tilapias: Hematological, immunological and microbiological parameters
Keywords: Bacillus subtilis; Bacillus toyoi; Cichlid; Macrophage migration